RENCANA PEMBANGUNAN GEREJA PANTEKOSTA PUSAT SURABAYA DI KOTA PALU SULAWESI TENGAH DALAM DINAMIKA HUBUNGAN ANTARUMAT BERAGAMA - Ibnu Hasan Muchtar (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
This study was carried out in order to find a model for overcoming many cases of conflicts among different religious community when building praying houses. The case study in the form of qualitative research has been used to get data. This study was on a plan to build a church by Pantecoast sect of Surabaya (GPPS)in Palu, that is opposed by local community.. Results of study shows that there is manipulated data on pupulation acceptance of building of the church. This conflict was not yet over since the agreement among the difference religious community that is facilitated by government, is not settled. The main reference of that agreement is co-ministries Regulation of Domestic Affairs and Religious Affairs no 8 and 9, year 2006.